Pemanfaatan aplikasi tiktok terhadap peningkatan penjualan produk kreatif - Karlin, Mochammad Karlin; Nurdiana, Ratna; Suryanto, Hadi (PPPM STKIP PGRI Lamongan, 2023)
Social media has a positive impact, namely making it easier to exchange information and making it easier to obtain online literature. Tiktok is a social networking application and music video platform from China which was launched in September 2016. This application is used by users to create their own short music videos. Welding at SMK Negeri 2 Lamongan in 2023. The hypothesis in this research is